An Improved Image Watermarking by Modifying Selected DWT-DCT Coefficients - Ernawan, Ferda; Ariatmanto, Dhani; Firdaus, Ahmad (IEEE, 2021)
Digital images can be easily copied or manipulated by irresponsible persons. The right property needs to be secured and protected from illegal copies and piracy. Digital watermarking is one of the solutions to protect the intellectual property of digital images. This paper proposed the adaptive scaling factor based on selected DWT-DCT coefficients of its image content. The adaptive scaling factor was generated based on the role of selected DWT-DCT coefficients against the average value of DWT-DCT coefficients. The watermark image was embedded by using a proposed set of rules that consider the adaptive scaling factor. The experimental results showed that the proposed scheme achieved high PSNR value of 47dB, SSIM value of about 0.987 and an embedded watermark resistance to several attacks in the watermarked image.